Immediate effects on adult drinkers of exposure to alcohol harm reduction advertisements with and without drinking guideline messages: experimental study - Wakefield, M.; Brennan, E.; Dunstone, K.; Durkin, S.; Dixon, H.; Pettigrew, Simone; Slater, M. (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 Society for the Study of Addiction Aims: To compare the immediate effects on drinkers of television advertisements focusing upon short- versus long-term harms with and without low-risk drinking guidelines. Design: Between-participants on-line experiment, with random assignment to view: (a) alcohol product advertisements (ALC control); (b) advertisements unrelated to alcohol (NON-ALC control); (c) advertisements featuring short-term harms (STH) of alcohol; (d) advertisements featuring STH plus a STH guideline (STH+G); (e) advertisements featuring long-term harms (LTH); or (f) advertisements featuring LTH plus a LTH guideline (LTH+G). Setting: Australia, 2016. Participants: A total of 3718 drinkers aged 18–64 years (48.5% male). Measurements: Post-exposure likelihood that participants provided a correct estimate of drinking levels associated with short- and long-term harms; post-exposure intentions to avoid alcohol or reduce consumption. Findings: After exposure to STH+G or LTH+G advertisements, participants were more likely to estimate correctly rather than overestimate drinking levels associated with harm, compared with those exposed to STH (P  <  0.001) and LTH advertisements without guidelines, respectively (P = 0.019) and ALC control (STH+G, P  <  0.001; LTH+G, P  <  0.001) and NON-ALC control conditions (STH+G, P  <  0.001; LTH+G, P = 0.011). Drinkers exposed to STH conditions were more likely to intend to reduce next-week alcohol consumption than those exposed to ALC control (both P  <  0.001) and NON-ALC control conditions (STH, P = 0.001; STH+G, P  <  0.001); a similar pattern was observed for intentions to avoid alcohol. Drinkers exposed to LTH conditions were al so more likely than drinkers exposed to ALC or NON-ALC controls to intend to avoid and reduce alcohol in the next week. Additionally, drinkers exposed to LTH+G were more likely to intend to reduce drinking than those exposed to LTH advertisements without guidelines (P = 0.022). Response patterns for low- and high-risk drinkers by condition were similar. Conclusions: Alcohol harm television advertisements increase intentions to reduce alcohol consumption among both low- and high-risk drinkers. The addition of low-risk drinking guidelines can enhance these effects for advertisements featuring long-term harms and improve estimates of both short- and long-term harmful drinking levels.